Community Development as the Resolution to the Environmental Crisis in Kampung Jawa, Riau Province, Indonesia - Rosilawati , Yeni; Dewi, Asri (International Journal of Psychosocial Rehabilitation, 2020)
Environmental issues are currently becoming more complex. In conjunction with the development of various industries, the resulting impact that occurs in the aspects of pollution, waste, infrastructure, and social ills has gone from bad to worse. Especially in the Riau Province, well known for the peatland fires which took place over the last few years. This paper aims to identify the community development programs undertaken in resolving the environmental crisis faced, as implemented in the Kampung Jawa Village, Bengkalis Regency, Riau Province. This paper features a qualitative approach, specifically the use of the case study method. This includes participatory observation and in-depth interviews that were conducted with the local community. Secondary data was gathered in the form of information about programs from newspaper clippings and reports. The research found that community development programs were successfully implemented through certain projects that were initiated by the local communities in order to change the popular mindset that peatlands are a source of disasters to one which highlights its economic potential. The community development programs conducted by the local communities are as follows: (i) Masyarakat Peduli Api (MPA), a community of volunteers seeking to deal with natural disasters and suppress forest fires. (ii) Pineapple Farms and Pineapple product processing (iii) Peat Arboretum. This study also found that community development efforts carried out stirred proactive dialogue and engagement with stakeholders which includes the farming community, other local communities, NGOs and local government.